1997
DOI: 10.1079/bjn19970178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary L-carnitine on the performance and egg quality of laying hens from 65–73 weeks of age

Abstract: The effects of L-carnitine supplementation (50-500 mg/kg diet) of a practical layer diet, based on maize, soyabean and wheat, on the performance of laying hens and some indices of egg quality were studied for 8 weeks, using 65-week-old hens kept in cages. Albumen quality (albumen height and Haugh (1937) unit score) was improved, while yolk index and yolk colour score were not affected by dietary L-carnitine. The percentage of egg-white increased and that of egg yolk decreased in response to dietary supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
37
4
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 17 publications
22
37
4
2
Order By: Relevance
“…In conformity with the results of this study, carnitine (Leibetseder, 1995;Rabie et al, 1997;Çelik et al, 2003) and humate (Yörük et al, 2004) supplementation had no effect on the feed consumption of laying hens. Some researchers also found that the values of feed consumption in broilers were not affected by humate (Yalçın et al, 2003;Özçelik and Yalçın, 2004), carnitine (Buyse et al, 2001;Lien and Horng, 2001;Özçelik and Yalçın, 2004) and carnitine + humate (Özçelik and Yalçın, 2004) supplementation.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In conformity with the results of this study, carnitine (Leibetseder, 1995;Rabie et al, 1997;Çelik et al, 2003) and humate (Yörük et al, 2004) supplementation had no effect on the feed consumption of laying hens. Some researchers also found that the values of feed consumption in broilers were not affected by humate (Yalçın et al, 2003;Özçelik and Yalçın, 2004), carnitine (Buyse et al, 2001;Lien and Horng, 2001;Özçelik and Yalçın, 2004) and carnitine + humate (Özçelik and Yalçın, 2004) supplementation.…”
Section: Resultssupporting
confidence: 71%
“…Similarly, some researchers found that L-carnitine (Leibetseder, 1995; Rabie et al, 1997;Çelik et al, 2003) had no significant effect on egg production of laying hens. However, the egg production values of laying quails fed 500 ppm L-carnitine (Bayram et al, 1999) and of laying hens fed 0.1 and 0.2% humate (Yörük et al, 2004) and fed 0.1, 0.2, 0.3 and 0.4% humate (Tancho, 1999) were higher than those of the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Günlük erkek hindi palazları ile 21 günlük yapılan bir çalışmada (4) canlı ağırlığın rasyona 50 ve 100 mg/kg düzeylerinde L-karnitin ilavesi ile etkilenmediğini bildiren bulgularıyla da uyum içerisindedir. Buna karşılık bazı araştırıcılar da (13,24,25,27) broyler rasyonlarına L-karnitin ilavesinin canlı ağırlık artışını olumlu yönde etkilediğini kaydetmişlerdir.…”
Section: Tartışma Ve Sonuçunclassified
“…Aksine bazı araştırmalarda ise herhangi bir etkisinin görülmediği bildirilmiştir (9,18,25,27). Karnitinin hindiler üzerinde yapılan çalışma ise sınırlıdır (4).…”
Section: Introductionunclassified